2008
DOI: 10.1557/proc-1107-199
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of Cation Distribution in HLW Wasteform Glass

Abstract: Magic-angle-spinning NMR has been used to establish the structural roles of various cations added to the borosilicate glass which is used for the vitrification of high-level nuclear waste (HLW). Representative surrogate oxides with nominal valencies of +1, +2 and +3 have been studied which span the range of oxides from modifier to intermediate and conditional glassformer. NMR has been carried out on those nuclei which are accessible and the species observed have been correlated with the physical and chemical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…[104] These results indicate that increasing the fraction of reedmergnerite or danburite c.r.s. in a glass should increase its durability.…”
Section: Srnl-sti-2009-00626mentioning
confidence: 89%
See 2 more Smart Citations
“…[104] These results indicate that increasing the fraction of reedmergnerite or danburite c.r.s. in a glass should increase its durability.…”
Section: Srnl-sti-2009-00626mentioning
confidence: 89%
“…99 NMR has indicated that glasses with more Q 3 than Q 4 silicate groups ww increase the dissolution rate of HLW glass. 103 The presence of Al, promotes Q 4 , reduces Q 3 , and reduces N 4 (the number of BO 4 tetrahedral groups). The presence of alkali and alkaline earth oxides increases Q 3 .…”
Section: Advances In Defining the Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of Al2O3-B2O3-Na2O-SiO2 glasses has been reported in the literature using nuclear magnetic resonance (NMR) and optical characterization techniques (see, for example [1,2]). The structure of Al2O3-B2O3-Na2O-SiO2 glasses has been reported in the literature using nuclear magnetic resonance (NMR) and optical characterization techniques (see, for example [1,2]).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of Al 2 O 3 -B 2 O 3 -Na 2 O-SiO 2 glasses has been reported in the literature using nuclear magnetic resonance (NMR) and optical characterization techniques [5,6]. The published work has been successful in identifying compositionally driven coordination changes in aluminum and boron, changes in the fraction of non-bridging oxygens, and the tendency for sodium to preferentially associate with aluminum.…”
Section: Introductionmentioning
confidence: 99%